SITUATION OF ROMANIAN ROMA LIVING IN ENCAMPMENTS IN POLAND AND OPPORTUNITIES OF PARTICIPATION IN SPORTING ACTIVITIES THE CASE OF POZNAŃ - Czarnota, Katarzyna (Society Register, 2018)
The phenomenon of migration and the challenges in the new hosting country have been often analysed in relation to the newcomers arriving from states outside of the European Union. However, in Poland these are the citizens of the EU who face discrimination. At the same time, despite the principles of the EU programs concerning different spheres and operations of integrative and inclusive character aimed at foreign nationals, including sport initiatives, Roma have been systematically omitted and excluded since the 1990s. This situation caused this group to be deprived of the right to work, health care, welfare and adequate housing and education. Opportunities of participating in sporting activities are very limited. In Poland, only a few non-governmental organisations and anti-racist activist initiatives attempt to cooperate with the members of this community. The first part of the article contains a broad introduction to the situation of Romanian Roma in Poland which is necessary in the light of the lack of studies on this subject within Polish sociology, and allows the reader to grasp the wider context of the discussion on the issue of access to sporting activities. Then, drawing on the research and activist experience, the author describes local sport initiatives available to Roma children living in the Poznań encampment, with emphasis on informal initiatives.